2019
DOI: 10.4174/astr.2019.97.6.282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraoperative neuromonitoring on efficacy and safety using sugammadex in thyroid surgery: randomized clinical trial

Abstract: PurposeThe use of nondepolarizing neuromuscular blocking agents (NMBAs) may affect intraoperative neuromonitoring (IONM) during anesthesia used during thyroid and parathyroid surgery.MethodsThe use of sugammadex was evaluated in a prospective clinical study during thyroid surgery. Between July 2018 and January 2019, 129 patients were prospectively randomized to either the sugammadex group (group B) or the control group (group A). Group A patients underwent standardized IONM during thyroidectomy, while group B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…For nerve sparing, meaningful qualified IONM should be performed during thyroid surgery, as well as the prevention of unwanted intraoperative bucking movement. The signals of V1 and R1 in the patients who received 1 mg/kg sugammadex in the present study were similar to those reported in previous studies in which 2 mg/kg sugammadex was used for reversal of neuromuscular blockade 2,3 . Additionally, the surgeon evaluated the quality of IONM in patients of the group I as good while assessing the EBSLN response in the present study.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…For nerve sparing, meaningful qualified IONM should be performed during thyroid surgery, as well as the prevention of unwanted intraoperative bucking movement. The signals of V1 and R1 in the patients who received 1 mg/kg sugammadex in the present study were similar to those reported in previous studies in which 2 mg/kg sugammadex was used for reversal of neuromuscular blockade 2,3 . Additionally, the surgeon evaluated the quality of IONM in patients of the group I as good while assessing the EBSLN response in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Unsuccessful IONM has been reported to occur at a rate of 3.8% to 23% in previous studies, 7–10 and one of the common reasons for unsuccessful IONM could be failure of neuromuscular blockade recovery. In general, 0.6 mg/kg rocuronium combined with 2 mg/kg sugammadex has been recommended for optimal conditions for both tracheal intubation and high‐quality IONM 2–4 . However, we occasionally observed intraoperative bucking when we used 2 mg/kg sugammadex, and 35.3% of patients in group II had bucking in this study.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations